ANALISIS MODEL PEMILIHAN MODA TRANSPORTASI UMUM TRAVEL DENGAN RUTE SUMBAWA-MATARAM - Erlina Damayanti; Eti Kurniati (Hexagon, 2023)
The population in Sumbawa increases every year which encourages various activities to use modes of transportation. Activities carried out such as mobility to areas that have attractions from various sectors such as Mataram, which is the capital city of West Nusa Tenggara Province. One of the modes of transportation that is widely used on the Sumbawa-Mataram route is travel which is a mode of transportation with relatively expensive rates. The description of the characteristics of travel passengers shows that 59% of travel users are women and 41% are men, with a vulnerable age of 20-29 years, then the last education is S1/S2/S3, with an income of IDR 1,000,000 – IDR. 2,000,000, most of whom own motorbikes, travel for business/work purposes, and use travel because of convenience. From the survey results using the State Preference method, the travel selection model is obtained in the form of a formulation in the form of multiple linear regression which reflects the utility value of travel selection, namely Y = 7.251 + (-0.078) X1 + 0.127X2 + 0.908X3. Then the utility and probability values are obtained for each model so that it is concluded that the travel selection model costs Rp. 140,000, a departure schedule of 5 times a day and a service consisting of 6 items is the model for choosing the best public transportation mode for the Sumbawa-Mataram route with a utility of 2.41 resulting in a probability of 92%, which is the best travel choice for the Sumbawa-Mataram route